Nonrejection pathology of renal allograft biopsies: 10 years experience from a tertiary care center in north India - Kandathil Joseph Philip; Nalini Calton; Basant Pawar (Wolters Kluwer Medknow Publications, 2011)
Background: Renal dysfunction in allograft transplant is common and its assessment is done using Revised Banff '97 working classification, which is the accepted formulation for the evaluation of histological appearance of renal allograft biopsies. The nonrejection category under the Banff working classification of renal allograft pathology forms a large group resulting in allograft dysfunction. Aim: To evaluate the spectrum of histopathological changes seen in renal allograft dysfunction. Materials and Methods: A total of 119 renal biopsies were studied over 10 years presenting with renal allograft dysfunction from a tertiary center in North India. Results: Majority of the biopsies were in the nonrejection category (47.1%), which included few cases of acute tubular necrosis (25.2%), cyclosporine nephrotoxicity (16%), infections (10.9%), and thrombotic microangiopathy (3.4%). The second largest category in our study was acute/active cellular rejection group (31.9%), which displayed moderate to severe tubulitis, mononuclear cell infiltrate in the interstitium, and vasculitis. Antibody-mediated rejection cases were seen in 28.6% of the renal biopsies followed by chronic allograft nephropathy cases (12.6%) showing features of tubular atrophy and interstitial fibrosis. Borderline changes with features of mild tubulitis contributed to 7.6% of the biopsies. The smallest group comprised of only 4.2%, which were within normal histological limits. Conclusion: Timely accurate diagnosis of renal allograft dysfunction is essential for prompt, effective management of renal transplant patients. Thus, nonrejection pathology forms a significant cause of renal dysfunction in patients with renal allograft transplantation.